Toward a Definition of Moving-Picture Dance - Carroll, No (The International Journal of Screendance, 2018)
This article was originally presented as a paper at the "Dance for the Camera Symposium" at the University of Wisconsin–Madison in 2000, and subsequently published in the Summer 2001 issue of Dance Research Journal. It was reprinted by Parallel Press, an imprint of the University of Wisconsin-Madison Libraries, as part of The International Journal of Screendance, Volume 1 (2010), Parallel Press. It is made available here with the kind permission of Parallel Press.